Observations of vertical eddy diffusivities in a shallow tropical reservoir - Yang, Peipei (2015)
Tropical lakes are of key importance as fresh water supply sources in tropical regions. One of the biggest threats to tropical lakes is nuisance algal blooms which at times can be harmful to human health. Research shows that thermal and flow dynamics, through their effects on the light and nutrient accessibility to phytoplankton, have a strong bearing on the growth of phytoplankton. We report herein results combining long-term and short-term observations of vertical diffusivities which impact the evolution of the surface mixed layer and the vertical transport of nutrients for a shallow tropical reservoir, Kranji Reservoir in Singapore.